DOI: 10.17077/etd.wsyy1po3
|View full text |Cite
|
Sign up to set email alerts
|

An Investigation of vertical scaling with item response theory using a multistage testing framework

Abstract: Beard, Jonathan James. "An Investigation of vertical scaling with item response theory using a multistage testing framework." PhD (Doctor of Philosophy) thesis,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 65 publications
0
2
0
Order By: Relevance
“…For convenience, the competence scores of the two measurement occasions were generated to be on the same scale. The distributional parameters of the two competence variables were based on results from NELS (Beard, ). A multivariate normal distribution was assumed with a mean of 0 and a variance of 1 for the ability distribution in Wave 1 and a mean of .4 and a variance of 1.1 in Wave 2.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…For convenience, the competence scores of the two measurement occasions were generated to be on the same scale. The distributional parameters of the two competence variables were based on results from NELS (Beard, ). A multivariate normal distribution was assumed with a mean of 0 and a variance of 1 for the ability distribution in Wave 1 and a mean of .4 and a variance of 1.1 in Wave 2.…”
Section: Methodsmentioning
confidence: 99%
“…Not many studies have investigated the performance of lMST. One simulation study performed by Beard () investigated the performance of lMST compared to CT in longitudinal designs. He found that lMST results in a smaller standard error for both ability and growth scores as compared to CT.…”
mentioning
confidence: 99%